2022
DOI: 10.3390/jcm11092289
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic Trends of Thalassemia, 2006–2018: A Nationwide Population-Based Study

Abstract: Thalassemia is the most common form of hereditary anemia. Here, we aimed to investigate the 13-year trend of the epidemiologic profiles and risk of comorbidities in thalassemia using a nationwide population-based registry in Korea. Diagnosis of thalassemia, the comorbidities and transfusion events in patients with thalassemia were identified in the Korean National Health Insurance database, which includes the entire population. The prevalence of thalassemia increased from 0.74/100,000 in 2006 to 2.76/100,000 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…, and Myanmar, as well as areas between southern China, Thailand, Peninsular Malaysia, the Pacific Islands, and Indonesia (Fabiana Meijon Fadul, 2019). Based on the World Health Organization (WHO) report in 2006, around 7% of the world's population is suspected of being a carrier of thalassemia and around 300,000 -500,000 babies are born with this disorder every year [4]. Based on data according to the Ministry of Health (2020), the number of thalassemia cases in Indonesia is 234,888 sufferers (Indonesian Ministry of Health, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…, and Myanmar, as well as areas between southern China, Thailand, Peninsular Malaysia, the Pacific Islands, and Indonesia (Fabiana Meijon Fadul, 2019). Based on the World Health Organization (WHO) report in 2006, around 7% of the world's population is suspected of being a carrier of thalassemia and around 300,000 -500,000 babies are born with this disorder every year [4]. Based on data according to the Ministry of Health (2020), the number of thalassemia cases in Indonesia is 234,888 sufferers (Indonesian Ministry of Health, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Beta-thalassemia has a global distribution as a consequence of population migration, and its prevalence fluctuates among different populations. It is more prevalent in the Mediterranean region, the Middle East, parts of North and sub-Saharan Africa, the Indian subcontinent, and Southeast Asia [4][5][6]. The overall prevalence of betathalassemia in India with an average of 3%-4% with an estimate that around 10,000-12,000 children are born every year with beta-thalassemia major and around 42 million are beta-thalassemia carriers [7].…”
Section: Introductionmentioning
confidence: 99%
“…Thalassemias are more common in populations of Mediterranean, African and Southeast Asian ancestry, where the gene mutations that cause the disorder are more prevalent 6 . The prevalence of thalassemias varies among different populations, with estimates ranging from .2% to 15% 7 . Left ventricular diastolic dysfunction has been reported in patients with thalassemia major in the early stage of myocardial damage 8 .…”
Section: Introductionmentioning
confidence: 99%
“…6 The prevalence of thalassemias varies among different populations, with estimates ranging from .2% to 15%. 7 Left ventricular diastolic dysfunction has been reported in patients with thalassemia major in the early stage of myocardial damage. 8 A small cohort study showed that patients with thalassemias had significantly lower LV-Sm and RV-Sm velocities and significantly higher levels of N terminal pro B type natriuretic peptide (NT-proBNP) compared to normal subjects.…”
mentioning
confidence: 99%